Gestational Diabetes Alters Functions in Offspring’s Umbilical Cord Cells With Implications for Cardiovascular Health - Amrithraj, Ajith Isaac; Kodali, Anjaneyulu; Nguyen, Linh; Teo, Adrian Kee Keong; Chang, Cheng Wei; Karnani, Neerja; Ng, Kai Lyn; Gluckman, Peter D.; Chong, Yap Seng; Stünkel, Walter (Endocrinology (Philadelphia), 2017)
Because noncommunicable diseases such as type 2 diabetes mellitus have their roots in prenatal development and conditions such as maternal gestational diabetes mellitus (GDM), we aimed to test this hypothesis in primary cells derived from the offspring of mothers with GDM compared with control subjects. We have assessed primary umbilical cord–derived cells such as human umbilical vein endothelial cells (HUVECs) and Wharton’s jelly–derived mesenchymal stem cells from the offspring of mothers with and without GDM. We have compared the primary isolates in cell-based assays measuring proliferation, mitochondrial oxygen consumption, and the ability to support blood vessel growth. We conducted gene expression microarray studies with subsequent pathway analysis and candidate gene validation. We observed striking differences between the two groups, such as lower metabolic rates and impairment of endothelial tube formation in cells with GDM background. HUVECs from subjects with maternal GDM have lower expression of the antiapoptotic protein BCL-xL, suggesting compromised angiogenic capabilities. Comparative gene expression analysis revealed blood vessel formation as a major pathway enriched in the GDM-derived HUVECs with the surface marker CD44 as a gene underexpressed in the GDM group. Functional validation of CD44 revealed that it regulates tube formation in HUVECs, thereby providing insights into a pathway imprinted in primary umbilical cord–derived cells from GDM offspring. Our data demonstrate that primary cells isolated from the umbilical cord of offspring born to mothers with GDM maintain metabolic and molecular imprints of maternal hyperglycemia, reflecting an increased risk for cardiovascular disease later in life.